Teaching French as a Foreign Language in Multilingual and Anglophone Contexts: The Experiences of Teachers in Nigeria and Ghana - Michael Akinpelu; Stella Afi Makafui Yegblemenawo (Educational Considerations, 2023)
Nigeria and Ghana are two Anglophone countries in West Africa that have adopted the teaching of the French language in their education systems because of their proximity to francophone countries and the necessity for regional integration. Whereas the language has gained some official status in the national curriculum (National Policy on Education) in Nigeria and made a required subject at some levels of education, French continues to enjoy a privileged status in Ghana but without an official status yet. Using a comparative approach, this paper explores the language policy in favour of the French language and its teaching at the secondary and post-secondary levels in both countries. The analysis of primary data collected with teachers at both levels in these countries show that, although French does not enjoy the same status in the two geographical spaces, similarities abound in terms of the policy regulating its teaching and the challenges impeding the full implementation of the policy. Country-specific solutions are offered to existing challenges.
Keywords: Anglophone setting; language policy; French; teaching; Nigeria; Ghana; multilingualism